Antimony uptake by mangroves and its environmental fate in the Sundarbans, India. (5th January 2021) - Mandal, S.K.; Ray, R.; González, A.G.; Pokrovsky, O.S.; Jana, T.K.
Abstract: Antimony (Sb), a naturally occurring trace element, tends to be enriched in the top-soil and contributes to soil contamination due to continued human activities. However, little is known about plant uptake of Sb, its storage in plant biomass and recycling in large littoral zones of tropical regions, subjected to strong anthropogenic impact. Biogeochemistry of Sb has been studied in the world's largest Sundarbans mangroves by measuring Sb concentration in sediment, plant organs, river water, sea water and pore water, and by determining Sb fluxes within the ecosystem reservoirs. Mangrove estuarine water and sediment appeared to be non-polluted in Sb as confirmed by their ecotoxicological indices. Sediment represented major pool of Sb (2170 g ha −1 ) compared to plant biomass (2.2 g ha −1 ). Antimony concentration (μg kg −1 ) in mangrove roots was highest (17 ± 6) followed by leaf and wood (10.5 ± 6, 9 ± 4, respectively, n = 24). Species-specific variability in Sb concentration was observed with Aegiceras corniculatum, showing highest concentration (48.8 μg kg −1 ) and Avicenna marina lowest (16.6 μg kg −1 ). Riverine input of Sb (9.3–12 Mg yr −1 ) was 3-order of magnitude higher than the mangrove sediment-derived input (0.02–0.05 Mg yr −1 ), suggesting the latter as negligible contributor of Sb to the Sundarbans coastal water. The mass balance calculations demonstrate that 63–88% of the annual riverine discharge of Sb export to the Bay of Bengal. Further biogeochemical studies should address Sb transport and speciation in surface waters and pore waters of this region. Highlights: Sb stock is determined in mangrove biomass and sediment. Sediment of the Sundarbans mangrove is the largest reservoir of Sb. Sb budget reveals strong sink capacity of the mangroves. Sb is recycled within the organic pool of the mangroves. Pollution indices reveal safe level of Sb in the mangrove ecosystem.